Factors that contribute to psychological resilience to suicidal thoughts and behaviours in people with schizophrenia diagnoses: qualitative study. Issue 5 (September 2019) - Harris, Kamelia; Gooding, Patricia; Haddock, Gillian; Peters, Sarah
Abstract : Background: Suicide is a leading cause of premature death in people with a diagnosis of schizophrenia. Although exposure to stressors can play a part in the pathways to death by suicide, there is evidence that some people with a diagnosis of schizophrenia can be resilient to the impact of suicide triggers. Aims: To investigate factors that contribute to psychological resilience to suicidal thoughts and behaviours from the perspectives of people with a diagnosis of schizophrenia. Method: A qualitative design was used, involving semi-structured, face-to-face interviews. Twenty individuals with non-affective psychosis or schizophrenia diagnoses who had experience of suicide thoughts and behaviours participated in the study. The interviews were audio-recorded, transcribed verbatim and examined using inductive thematic analysis. Results: Participants reported that psychological resilience to suicidal thoughts and behaviours involved ongoing effort. This ongoing effort encompassed: (a) understanding experiences (including reconciliation to mental health experiences and seeking reasons to live), (b) active behaviours (including talking to people and keeping occupied), and (c) relationship dynamics (including feeling supported by significant others and mental health professionals). Conclusions: Psychological resilience was described as a dynamic process that developed over time through the experiences of psychosis and the concomitant suicidal experiences. Psychological resilience can be understood using a multicomponential, dynamic approach that integrates buffering, recovery and maintenance resilience models. In order to nurture psychological resilience, interventions should focus on supporting the understanding and management of psychosis symptoms and concomitant suicidal experiences. Declaration of interest: None.